IMPLEMENTATION OF GOOD GOVERNANCE AND ITS EFFECT ON LOCAL GOVERNMENT TRANSPARENCY - Abdul Halil Hi Ibrahim; Iksan R.A. Arsad, Bakri La Suhu (Adisam Publisher, 2024)
This study aims to examine the effect of the application of Good Governance principles on local government transparency. In the context of good governance, principles such as accountability, participation, transparency, responsiveness, efficiency and equality are decisive factors in improving the quality of public services and public trust. This study uncovers the extent to which good governance practices contribute to improving local government transparency, which is one of the main factors in promoting democracy and sustainable socio- economic development. This study used a qualitative approach with a literature research method. This study found that the implementation of good governance has a significant influence on local government transparency. Good governance principles such as public participation, accountability, and transparency are proven to improve the quality of information provided to the public, facilitate social monitoring, and strengthen public trust in government institutions.